Reconstruction of Potential in Discrete Sturm-Liouville Problem - Koyunbakan, Hikmet (Springer Basel Ag, 2022)
In this paper, we consider the Sturm-Liouville problem with Dirichlet conditions in the case of time scales consists isolated points. Then, we obtain discrete Sturm-Liouville problem on a finite interval. We solve the inverse nodal problem, especially give a reconstruction formula for the potential function q.
Keywords: Sturm Liouville difference equation; Nodal points; Potential